STRES PADA PENDUDUK LANJUT USIA YANG MENDERITA HIPERTENSI DIWILAYAH KERJA PUSKESMAS TABANAN II KABUPATEN TABANAN PERIODE SEPTEMBER- OKTOBER 2013 - Andy Wiraputra (Intisari Sains Medis, 2015)
The growing number of the elderly population, so health related problems also will increase. Mental health concerns are among the most important health problems in the management of the elderly. From research was found that people who experience stress have a higher risk of developing hypertension, 2.5 times more than those who do not experience stress. In May 2013, 54% of elderly people in the region in tabanan second primary health center’s region at tabanan regency have been diagnosed with hypertension,.This study aims to determine the relationship of stress on the degree of hypertension, that suffered by elderly people treated at in Tabanan second primary health center’s region at Tabanan regency. The study carried out in September-October 2013, using a study design with cross sectional analysis. Data collection in the study was done in two stages of work, primary data through interviews conducted by questionnaires from house to house and secondary data obtained from the information available at primary health center’s . The results showed that the respondents with hypertension, grade I status as many as 41 people (75.9%) experienced stress while respondents with hypertension, grade II status as many as 27 people (81.8%) experienced stress. Kendall correlation test results for the variable stress levels with the degree of hypertension, showed a correlation coefficient of 0.069 with p = 0.521. These results show a correlation between stress and the the degree of hypertension, in the same direction. However, the price of the correlation coefficient between stress and the degree of hypertension showed a very weak relationship between stress and the degree of hypertension, (0.069 <0.2). When viewed from the price of p = 0.521 (> 0.05) so there is no significant correlation between the two variables.